Biofortification of field-grown cassava by engineering expression of an iron transporter and ferritin - Narayanan, Narayanan; Beyene, Getu; Chauhan, Raj Deepika; Gaitán-Solís, Eliana; Gehan, Jackson; Boy, Erick (Nature Publishing Group, 2019)
Less than 10% of the estimated average requirement (EAR) for iron and zinc is provided by consumption of storage roots of the staple crop cassava (Manihot esculenta Crantz) in West African human populations. We used genetic engineering to improve mineral micronutrient concentrations in cassava. Overexpression of the Arabidopsis thaliana vacuolar iron transporter VIT1 in cassava accumulated three- to seven-times-higher levels of iron in transgenic storage roots than nontransgenic controls in confined field trials in Puerto Rico. Plants engineered to coexpress a mutated A. thaliana iron transporter (IRT1) and A. thaliana ferritin (FER1) accumulated iron levels 7–18 times higher and zinc levels 3–10 times higher than those in nontransgenic controls in the field. Growth parameters and storage-root yields were unaffected by transgenic fortification in our field data. Measures of retention and bioaccessibility of iron and zinc in processed transgenic cassava indicated that IRT1 + FER1 plants could provide 40–50% of the EAR for iron and 60–70% of the EAR for zinc in 1- to 6-year-old children and nonlactating, nonpregnant West African women.